Influence of substitution for on the microwave dielectric properties of Mg2Al4Snx ceramics - Junbo Guo; Xiangpeng Wang; Yang Song; Leijun Yao; Chuanshi Min; Xiao Li; Fanshuo Wang; Yuanming Lai (Journal of Advanced Dielectrics)
The Mg2Al4[Formula: see text]Snx[Formula: see text] ([Formula: see text]) ceramics were successfully synthesized via the solid-state reaction method. The XRD results show that the main phase of the ceramics is Mg2Al4Si5[Formula: see text]. When [Formula: see text], there is a second phase of Al2SiO5. With the increase of x, the content of [Formula: see text] gradually increased, the Al2SiO5 phase disappeared, and the SnO2 and MgAl2O4 phases appeared. In addition, the cell volume of the ceramic changes with the increase of x, which indicates that partial [Formula: see text] successfully enters the lattice with ion substitution and lattice distortion. The relative density and [Formula: see text] are highly correlated. The quality factor (Qf) is not only affected by the relative density but also by the symmetry of the [Si4Al2] ring. The bond strength as an evaluation of the stability of the crystal structure determines the magnitude of [Formula: see text]. Good microwave dielectric properties were achieved for samples at [Formula: see text] with sintering at 1400∘C: [Formula: see text], [Formula: see text][Formula: see text]GHz and [Formula: see text][Formula: see text]ppm/∘C, demonstrating that Mg2Al4[Formula: see text][Formula: see text][Formula: see text] ceramics are an ideal candidate for microwave electronics.